Exploiting the Degradation Mechanism of NCM523∥ Graphite Lithium‐Ion Full Cells Operated at High Voltage. Issue 2 (10th November 2020) - Klein, Sven; Bärmann, Peer; Beuse, Thomas; Borzutzki, Kristina; Frerichs, Joop Enno; Kasnatscheew, Johannes; Winter, Martin; Placke, Tobias
Abstract: Layered oxides, particularly including Li[Ni x Co y Mn z ]O2 (NCM xyz ) materials, such as NCM523, are the most promising cathode materials for high‐energy lithium‐ion batteries (LIBs). One major strategy to increase the energy density of LIBs is to expand the cell voltage (>4.3 V). However, high‐voltage NCM ∥ graphite full cells typically suffer from drastic capacity fading, often referred to as "rollover" failure. In this study, the underlying degradation mechanisms responsible for failure of NCM523 ∥ graphite full cells operated at 4.5 V are unraveled by a comprehensive study including the variation of different electrode and cell parameters. It is found that the "rollover" failure after around 50 cycles can be attributed to severe solid electrolyte interphase growth, owing to formation of thick deposits at the graphite anode surface through deposition of transition metals migrating from the cathode to the anode. These deposits induce the formation of Li metal dendrites, which, in the worst cases, result in a "rollover" failure owing to the generation of (micro‐) short circuits. Finally, approaches to overcome this dramatic failure mechanism are presented, for example, by use of single‐crystal NCM523 materials, showing no "rollover" failure even after 200 cycles. The suppression of cross‐talk phenomena in high‐voltage LIB cells is of utmost importance for achieving high cycling stability. Abstract : A worst‐case scenario : Lithium‐ion battery cells operated at high voltage typically suffer from drastic capacity fading. The degradation mechanisms responsible for cell failure are unraveled for NCM523 graphite cells operated at 4.5 V, and degradation is attributed to severe solid electrolyte interphase growth at graphite through deposited transition metals. These deposits induce the formation of Li metal dendrites, which, in the worst case, lead to (micro‐) short circuits.